2021
DOI: 10.3906/sag-2101-81
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced cytidine deaminase expression in patients with myelodysplastic syndrome and its relationship with prognosis and treatment

Abstract: Background and Aim: Activation induced cytidine deaminase (AID) enables antibody diversity in B lymphocytes. It may also have an effect on MDS pathogenesis by causing somatic mutations and by inducing epigenetic changes in myeloid cells. This study aimed to compare AID expression of MDS patients with healthy controls, of MDS patients in different risk groups and of MDS patients according to their treatment.Materials and Methods: Total RNA was isolated and complementary DNA (cDNA) was transcribed from the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…CDA activity was lower in AML patients compared to MDS patients, for which we have no explanation so far. We can hypothesise firstly a blastic clearance of CDA, secondly a role in the physiopathology of the disease with increased CDA expression in the peripheral blood of MDS patients compared to healthy controls 20 with more severe disease in deficient patients and thirdly a possible role of PNN in CDA synthesis. Here, in contrast to some previous clinical reports, no gender effect on CDA activities was found 21 .…”
Section: Discussionmentioning
confidence: 99%
“…CDA activity was lower in AML patients compared to MDS patients, for which we have no explanation so far. We can hypothesise firstly a blastic clearance of CDA, secondly a role in the physiopathology of the disease with increased CDA expression in the peripheral blood of MDS patients compared to healthy controls 20 with more severe disease in deficient patients and thirdly a possible role of PNN in CDA synthesis. Here, in contrast to some previous clinical reports, no gender effect on CDA activities was found 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on myelodysplastic syndrome and myeloproliferative neoplasms have found a strong association between AID overexpression and these malignancies (14,17)…”
Section: Discussionmentioning
confidence: 92%
“…Numerous reports are found stating deregulated AID activity to be able to induce various types of cancer, mainly as a result of its overexpression (11)(12)(13)(14). This study aimed to identify the state of AID expression in CML patients and to reveal AID's etiopathogenic role, which is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%